INTER-SECTOR COLLABORATION IN EDUCATION: ANALYSING OPPORTUNITIES AND BARRIERS THROUGH A LITERATURE REVIEW - Abdul Haq AS; Loso Judijanto; Darma Jasuli (Adisam Publisher, 2026)
This research explores the opportunities and barriers to intersectoral collaboration in education through a literature review. Collaboration between the education, business and government sectors was identified as providing a number of benefits, including increased resources, innovation in teaching methods and relevance of education programmes to labour market needs. However, there are various barriers that need to be overcome in order to achieve optimal results. These include differences in objectives between sectors, bureaucratic constraints, funding issues, ineffective communication and differences in organisational culture. This study emphasises the importance of commitment, open communication and flexible framework design to overcome these challenges and maximise the potential of intersectoral collaboration in education.